Astragaloside IV Ameliorates Myocardial Infarction Induced Apoptosis and Restores Cardiac Function - Sun, Chuang; Zeng, Guangwei; Wang, Tingting; Ren, He; An, Huixian; Lian, Cheng; Liu, Jing; Guo, Li; Li, Wei (Frontiers in Cell and Developmental Biology, 2021)
Background: Type 2 diabetes mellitus (T2DM) increases the risk of cardiovascular disease including myocardial infarction (MI). Inflammation and apoptosis have been implicated in the pathophysiology of MI. In the present study, the effects of astragaloside IV (AS-IV) on MI in the diabetic mice were evaluated. Methods: High glucose/high fat (HG/HF) and hypoxia culture condition were established to mimic diabetic condition. After administration of AS-IV to H9c2 myocytes, the cell apoptosis, viability and activation of MAPK signaling pathways were detected. MI was induced in Streptozotocin-induced diabetic mice. After administration of AS-IV to mice, cardiac function, cardiac fibrosis, inflammation, and activation of MAPK signaling pathway were detected. Results: AS-IV treatment significantly inhibited HG/HF and hypoxia-induced apoptosis of H9c2. AS-IV inhibited activation of JNK and p38 signaling pathway while promoted the activation of EKR signaling pathway. AS-IV treatment rescued cardiac function, suppressed cardiac fibrosis and inflammation, and differently regulated the activation of MAPK signaling pathways. Conclusion: AS-IV prevented apoptosis and restores cardiac function in MI, which may be due to the regulation of MAPK signaling pathway in diabetes.